The Effect of Storage Time Based on Fruit Age on The Viability of Papaya Seeds (Carica papaya) on The Potential to Grow - Ulfia Asri; Muhibbuddin Muhibbuddin; Hasanuddin Hasanuddin; Cut Nurmaliah; Supriatno Supriatno (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
AbstractPapaya (Carica papaya) is one of the plants from the Caricaceae family that lives in lowland areas, dry places and wet places. Papaya is a cultivated plant with a seedling process, quality seeds are obtained from physiologically ripe fruit by taking into account the age of the fruit and the duration of seed storage. This study aims to determine the effect of storage time of papaya seeds on the viability of papaya seeds, determine the effect of fruit age on the viability of papaya seeds, and determine the interaction between storage time and fruit age on the viability of papaya seeds (Carica papaya). This research was conducted in September 2021-January 2022. The method used was an experiment with a Factorial Completely Randomized Design (CRD). The first factor was fruit age consisting of 3 levels, namely P1 = 90 DAS, P2 = 100 DAS, and P3 = 110 DAS, and the second factor was storage time consisting of 4 levels, namely L1 = No storage, L2 = 14 days, L3 = 21 days, and L4 = 28 days. The object of this research is in the form of papaya seeds (Carica papaya) obtained from the Ladong area, Mesjid Raya District, Aceh Besar District. The parameters of this research are growth potential. Data analysis used analysis of variance (ANOVA) and further test at a significant level of 0.05. The results showed that storage time affects the viability of papaya seeds on growth potential, fruit age affects the viability of papaya seeds, namely growth potential, and there is an interaction between storage time and fruit age on the viability of papaya seeds on potency. AbstrakPepaya (Carica papaya) adalah tumbuhan dari familia Caricaceae yang berhabitat di kawasan dataran rendah, ditempat kering dan ditempat basah. Pepaya merupakan tanaman budidaya dengan proses pembibitan, bibit bermutu didapatkan dari buah yang masak fisiologis dengan memperhatikan umur buah dan lama penyimpanan benih. Tujuan penelitian untuk mengetahui pengaruh lama penyimpanan biji pepaya terhadap viabilitas biji pepaya, mengetahui pengaruh umur buah terhadap viabilitas biji pepaya, dan mengetahui interaksi antara lama penyimpanan dengan umur buah terhadap viabilitas biji pepaya (Carica papaya). Penelitian ini pada bulan September 2021 sampai Januari 2022. Metode dalam penelitian ini menggunakan eksperimen dengan Rancangan Acak Lengkap (RAL) faktorial. Faktor 1 adalah umur buah terdiri 3 taraf yaitu P1=90 HSM, P2=100 HSM, dan P3=110 HSM, dan faktor 2 adalah lama penyimpanan terdiri 4 taraf yaitu L1=Tanpa penyimpanan, L2=14 hari, L3=21 hari, dan L4=28 hari. Objek penelitian ini yaitu berupa biji pepaya (Carica papaya) yang diperoleh dari kawasan Ladong, Kecamatan Mesjid Raya, Kabupaten Aceh Besar. Parameter dari penelitian ini adalah potensi tumbuh. Analisis data menggunakan (ANAVA) dan uji lanjut taraf signifikan 0,05. Hasil penelitian menunjukkan lama penyimpanan berpengaruh terhadap viabilitas biji pepaya pada potensi tumbuh, umur buah berpengaruh terhadap viabilitas biji pepaya yaitu potensi tumbuh, dan terdapat interaksi antara lama penyimpanan dengan umur buah terhadap viabilitas biji pepaya pada potensi tumbuh.